Decreased intelligence in children and exposure to fluoride and arsenic in drinking water Disminución de la inteligencia en niños y exposición al flúor y arsénico en el agua potable - Diana Rocha-Amador; Maria Elena Navarro; Leticia Carrizales; Raúl Morales; Jaqueline Calderón (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Recent evidence suggests that fluoride (F) and arsenic (As) may adversely affect intelligence quotient (IQ) scores. We explore the association between exposure to F and As in drinking water and intelligence in children. Three rural communities in Mexico with contrasting levels of F and As in drinking water were studied: Moctezuma (F 0.8±1.4mg/L; As 5.8±1.3µg/L); Salitral (F 5.3±0.9mg/L; As 169±0.9µg/L) and 5 de Febrero (F 9.4±0.9mg/L; As 194±1.3µg/L). The final study sample consisted of 132 children from 6 to 10 years old. After controlling for confounders, an inverse association was observed between F in urine and Performance, Verbal, and Full IQ scores (beta values = -13, -15.6, -16.9, respectively). Similar results were observed for F in drinking water (beta values = -6.7, -11.2, -10.2, respectively) and As in drinking water (beta values= -4.30, -6.40, -6.15, respectively). The p-values for all cases were < 0.001. A significant association was observed between As in urine and Full IQ scores (beta = -5.72, p = 0.003). These data suggest that children exposed to either F or As have increased risks of reduced IQ scores. Estudios recientes sugieren que el flúor (F) y el arsénico (As) pueden tener efectos adversos sobre el coeficiente intelectual (CI). En este estudio exploramos la asociación entre el F y el As y la inteligencia en niños expuestos a estas sustancias a través del agua. Tres comunidades rurales de México con diferentes niveles de F y As fueron estudiadas: Moctezuma (F 0,8±1,4mg/L; As 5,8±1,3µg/L); Salitral (F 5,3±0,9mg/L; As 169±0,9µg/L) y 5 de Febrero (F 9,4±0,9mg/L; As 194±1,3µg/L). La muestra final fue de 132 niños de 6 a 10 años de edad. Después de controlar por confusores, se obtuvieron asociaciones inversas entre F en orina y las puntuaciones de los CI (Desempeño, Verbal y Total) (valores beta = -13, -15,6, -16,9, respectivamente) p < 0,001 en todos los casos. Resultados similares se obtuvieron con F en agua (valores beta = -6,7, -11,2, -10,2, respectivamente) y con As en agua (valores beta = -4,30, -6,40, -6,15, respectivamente). En todos los casos p < 0,001. Para As en orina, se obtuvo una asociación inversa con las puntuaciones del CI total (beta= -5,72; p = 0,003). Estos datos sugieren que los niños expuestos al F o al As tienen mayor riesgo de tener disminución en las puntuaciones del CI.